2021
DOI: 10.1016/j.compbiomed.2021.104364
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential antiviral compounds against SARS-CoV-2 structural and non structural protein targets: A pharmacoinformatics study of the CAS COVID-19 dataset

Abstract: SARS-CoV-2 is a newly discovered virus which causes COVID-19 (coronavirus disease of 2019), initially documented as a human pathogen in 2019 in the city of Wuhan China, has now quickly spread across the globe with an urgency to develop effective treatments for the virus and emerging variants. Therefore, to identify potential therapeutics, an antiviral catalogue of compounds from the CAS registry, a division of the American Chemical Society was evaluated using a pharmacoinformatics approach. A total of 49,431 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Apart from structural proteins, SARS-CoV-2 encodes several nonstructural proteins (NSP1 to NSP16) that are also known to play various important functions . Several studies have utilized MD simulations to investigate the effect and binding modes of approved and repurposed drugs, natural bioactive and metabolite molecules, and inhibitors against NSPs. However, as they are at the early stages of possible therapeutics development, it is outside the scope of the present perspective to discuss them in detail.…”
Section: Protein Interactions and Conformational Dynamicsmentioning
confidence: 99%
“…Apart from structural proteins, SARS-CoV-2 encodes several nonstructural proteins (NSP1 to NSP16) that are also known to play various important functions . Several studies have utilized MD simulations to investigate the effect and binding modes of approved and repurposed drugs, natural bioactive and metabolite molecules, and inhibitors against NSPs. However, as they are at the early stages of possible therapeutics development, it is outside the scope of the present perspective to discuss them in detail.…”
Section: Protein Interactions and Conformational Dynamicsmentioning
confidence: 99%
“…From our analysis it was observed that most publications have performed virtual screening on commercially available drugs ( Balasubramaniam and Schmookler Reis 2020 ; Borgio et al, 2020 ; Gurung 2020 ; Iftikhar et al, 2020 ; Ugurel et al, 2020 ; Abidi et al, 2021 ; Sundar et al, 2021 ; Alanazi et al, 2022 ; Azmoodeh et al, 2022 ) or natural products ( Kousar et al, 2020 ; Naik et al, 2020 ; Ahmad et al, 2021 ; James et al, 2021 ; Vivek-Ananth et al, 2021 ; Bhargavi et al, 2022 ; Hossain et al, 2022 ; Samdani et al, 2022 ). Other published works make use of fragments ( Freidel and Armen, 2021 ) or publicly available compound libraries ( Mirza and Froeyen, 2020 ; García et al, 2021 ; El Hassab et al, 2022 ; Pitsillou et al, 2022 ). It is recognized that multi-targeted approaches are often carried out, most notably including RNA-dependent RNA polymerase and 3CL protease, to have dual-target SARS-CoV-2 inhibitors.…”
Section: Main Considerationsmentioning
confidence: 99%
“…Advanced studies in the molecular biology of viruses have highlighted many potential targets for antiviral drugs (85). The efficacy of virus activity limiting drugs, such as Argovit, Triviron, Ecocid, and lauric acid monoglycerides, has been tested in chickens by inoculation of the vaccine strain of IBV H120 against IB of chickens.…”
Section: Use Of Virucidal Drugs Against Ibv Infectionmentioning
confidence: 99%